A Review of Factors Influencing Maturation of Atlantic Salmon, Salmo salar, with Focus on Water Recirculation Aquaculture System Environments. Issue 5 (9th August 2016) - Good, Christopher; Davidson, John
Abstract: Sexual maturation of Atlantic salmon, Salmo salar, is a complex process, with many variables having the capacity to influence the timing and prevalence of maturation and acting as promoters and/or inhibitors of sexual development. Precocious maturation has the capacity to seriously impact production in commercial aquaculture settings, and in response there has been a significant amount of research devoted to understanding this issue in order to develop remedial strategies. Very little research has been conducted specifically examining salmon maturation in land‐based, closed containment water recirculation aquaculture systems, which have recently received attention as an alternative technology for the sustainable production of market‐size Atlantic salmon. Unfortunately, the nascent closed containment salmon industry has thus far experienced high levels of precocious maturation, for reasons that are presently unclear. Given the economic challenges facing the closed containment industry's expansion, it is imperative that best management practices be developed to reduce economic losses from early maturation, in order to assist the sustainable growth of farmed Atlantic salmon production. This review provides a brief summary of published research on factors associated with early salmonid maturation, as well as information from research examining maturation and growout performance of Atlantic salmon in closed containment aquaculture systems.